Clay composition patterns and their influence on the adhesive strength of earthen plasters - García Villar, Gonzalo; Enzo, Marcial; Guillermo, Rolón (Revista de la Construcción. Journal of Construction, 2024)
The clay fraction of earthen plasters is the part responsible for the acquisition of cohesion and adherence that they possess against deterioration factors. Adherence is the property responsible for keeping the plaster together with the wall and is influenced by the percentage content of clay as well as by its mineralogy and the heterogeneity of minerals that may be present. However, it is still unknown in depth how clay minerals perform in the adherent properties of earthen plasters when the composition is heterogeneous in the material. The objective of this study is to evaluate the incidence of the mineralogical complexity of clay mineralogy in the variability of the adherence of earth plasters. To evaluate the variability, considering that the mineralogy of the soils depends directly on the place and the formation processes, eight soils from Tucumán (Argentina) corresponding to different physiographic units were analyzed. A methodology was designed for sample preparation that allows soils to be compared through adhesion tests. They were characterized by XRD to determine their mineralogical composition and by the hydrometric method to determine their granulometry. To evaluate the adherence of mixtures made with the respective soils, it was proposed in the first instance to compensate the granulometry of the soils to equate them and, once the plasters were made, this property was evaluated through shear and pull-off tests. The results showed that they allowed us to identify that the soils presented a pattern of mineralogical composition common to all the physiographic units, made up of the Ill and K pair, the former being predominant. For this pattern, it was observed in particular that there is a positive correlation between the increase in Ill content with the increase in the adhesive strength of the plasters. Clay minerals from the Sm group also contribute to the increase in adherence when the percentage is greater than or equal to 11%. On the contrary, K and Cl do not influence the increase in adhesive strength.The clay fraction of earthen plasters is the part responsible for the acquisition of cohesion and adherence that they possess against deterioration factors. Adherence is the property responsible for keeping the plaster together with the wall and is influenced by the percentage content of clay as well as by its mineralogy and the heterogeneity of minerals that may be present. However, it is still unknown in depth how clay minerals perform in the adherent properties of earthen plasters when the composition is heterogeneous in the material. The objective of this study is to evaluate the incidence of the mineralogical complexity of clay mineralogy in the variability of the adherence of earth plasters. To evaluate the variability, considering that the mineralogy of the soils depends directly on the place and the formation processes, eight soils from Tucumán (Argentina) corresponding to different physiographic units were analyzed. A methodology was designed for sample preparation that allows soils to be compared through adhesion tests. They were characterized by XRD to determine their mineralogical composition and by the hydrometric method to determine their granulometry. To evaluate the adherence of mixtures made with the respective soils, it was proposed in the first instance to compensate the granulometry of the soils to equate them and, once the plasters were made, this property was evaluated through shear and pull-off tests. The results showed that they allowed us to identify that the soils presented a pattern of mineralogical composition common to all the physiographic units, made up of the Ill and K pair, the former being predominant. For this pattern, it was observed in particular that there is a positive correlation between the increase in Ill content with the increase in the adhesive strength of the plasters. Clay minerals from the Sm group also contribute to the increase in adherence when the percentage is greater than or equal to 11%. On the contrary, K and Cl do not influence the increase in adhesive strength.